RIPLEY´S K FUNCTION AND MORAN INDEX ON SPATIAL DISTRIBUTION OF NATURAL REGENERATION OF CANDEIA IN MANAGED AREAS - ARAÚJO, Emanuel José Gomes de; PÉLLICO NETTO, Sylvio; MACHADO, Sebastião do Amaral; DALLA CORTE, Ana Paula; SCOLFORO, José Roberto Soares; DAVID, Hassan Camil; MORAIS, Vinícius Augusto (Brazilian Journal of Biometrics, 2016)
Considering the importance of knowing the spatial pattern of forest species, the aim of this study was to describe the spatial pattern of natural regeneration of the species Eremanthus erythropappus (DC) MacLeish (candeia), after the application of a management system with seed-trees. Data from 46 populations submitted to the management with seed-trees were collected in the southern region of Minas Gerais. In each population all candeia (regenerating individuals, the candeia trees and remained after a harvesting operation) and individuals trees of other species were recorded and georeferenced. In each regeneration was also measured the total height. It was also applied the univariate Ripley’s K index and the Moran index to describe the spatial regeneration pattern of candeia. To check the spatial relationship of regenerations with individual trees (candeia and other species) and the candeia strains it was applied the Ripley’s K bivariate function. The two methodologies presented similar results, indicating that the candeia pattern unit is predominantly aggregate and, in some cases, varies from aggregate to a random pattern. Furthermore, there is a predominant pattern of interaction between regeneration and the remaining stumps from removed trees in the forest management, meaning a relationship between the budding regeneration and the remaining stumps.